HUBUNGAN ANTARA PERSALINAN KETUBAN PECAH DINI DENGAN KEJADIAN ASFIKSIA NEONATORUM DI RSUD DR. SOESELO KABUPATEN TEGAL - Natiqotul Fatkhiyah (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2011)
This was an analytic survey research is a study that tries to explore how and why health phenomena  that  occur.  While  the  approach  used  is  a  cross  sectional  approach  is  to study the dynamics of correlation between risk factors with effects by way of approach, observation  or  data  collection  as  well  as  at  some  point.  Bivariate  analysis  results obtained with  2   2 count by 0.05 and db = 1, the obtained results  2 = 8.454 and p  =  0.004  for  values  count  more   2>  3.481  and  p  value  <0.05,  then  the  working hypothesis  which  states  there  is  a  relationship  between  premature  rupture  of membranes with acceptable incidence of asphyxia.  It can be concluded that premature rupture  of  membranes  variables  significantly  associated  with  incident  asphyxia  in newborns. the study following respondents who experienced PROM 23 people (21.3%) and  did  not  experience there  PROM 85  people  (78.7%)  respondents  who  experienced asphyxia  there  are  38  people  (35.2%)  and  the  did  not  experience  there  are  70  people asphyxia  (64.8%);  There  was  a  significant  correlation  between  premature  rupture  of membranes with  asphyxia neonatorum in newborns is x2 value of 8.454 and p value = 0.004. Keywords: Premature Rupture Ketupan, Neonatorum Asphyxia, Birth Mother